1991
DOI: 10.1038/bjc.1991.395
|View full text |Cite
|
Sign up to set email alerts
|

Influence of the antioestrogen tamoxifen on normal breast tissue

Abstract: Summary Immunohistochemical assays have been employed to study the expression of ER, PgR, EGFR and Ki67 immunostaining in normal breast tissue (n = 76). The expression of ER and PgR was highly variable in both pre and postmenopausal women and was characterised by large numbers of apparently negative cells. This was most evident for ER-ICA staining in tissues removed from premenopausal women. PgR levels were highest in the ducts of premenopausal women, while EGFR expression was elevated in both ducts and lobule… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0
2

Year Published

1994
1994
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(14 citation statements)
references
References 18 publications
1
11
0
2
Order By: Relevance
“…It is as yet unknown if such a phenotype arises from aberrant loss of the steroid hormone receptor, or if such tumours merely arise from the outgrowth of the ER-negative/EGFR-positive cells known to exist in the normal mammary epithelium (Walker et al 1991(Walker et al , 1992. Whatever the mechanism, it is believed that regulation of such tumours is severed from the oestrogenic environment and that they are initially wholly dependent on growth factor signalling for their mitogenic responses (Nicholson et al 1997).…”
Section: Loss Of Ermentioning
confidence: 99%
“…It is as yet unknown if such a phenotype arises from aberrant loss of the steroid hormone receptor, or if such tumours merely arise from the outgrowth of the ER-negative/EGFR-positive cells known to exist in the normal mammary epithelium (Walker et al 1991(Walker et al , 1992. Whatever the mechanism, it is believed that regulation of such tumours is severed from the oestrogenic environment and that they are initially wholly dependent on growth factor signalling for their mitogenic responses (Nicholson et al 1997).…”
Section: Loss Of Ermentioning
confidence: 99%
“…In our study fractional replacement rates were 0.69 ± 0.10% and 0.24 ± 0.08 % per day, respectively for pre-menopausal and postmenopausal women. Several studies have similarly found significantly lower proliferation rates in postmenopausal as compared to pre-menopausal women [33][34][35][36][37][38][39] as well as significant age related differences [35,40]. However, our small sample size may have precluded the ability to see a significant age correlation.…”
Section: Discussionmentioning
confidence: 67%
“…Existe a possibilidade de atenuação da sensibilidade da proliferação induzida por estradiol, mas não da expressão do RP na mama na pós-menopausa (44). Há evidências de que a expressão do RP seja sensível a baixos níveis de estradiol, enquanto que, para gerar resposta de proliferação celular, níveis mais altos talvez sejam necessários (45).…”
Section: Discussionunclassified